Epidemiologia dos carcinomas basocelulares excisados em um hospital terciário do Rio Grande do Sul - Neumaier, Luís Felipe Teixeira (2022)
Basal cell carcinoma (BCC) is a basaloid cell tumor originating from tumor stem cells of the epidermis, accounting for 70-80% of cutaneous neoplasms. It has local invasive behavior and low metastatic risk. The main risk factor is intermittent and intense sun exposure without protection. The diagnosis can be presumed by dermoscopy and should be confirmed with skin biopsy. Several treatments can be used, their indications vary according to the histological subtype. Surgical treatment is the one with the highest cure rates and allows the histological evaluation of the margins. We performed an observational, retrospective, and quantitative study whose objective was to describe the frequency and analyze the association between the epidemiological and histopathological findings of surgically excised BCCs. The study population consisted of patients who underwent surgical excision of lesions diagnosed as BCC at the Hospital Universitário de Santa Maria from January 1st, 2014, to December 31, 2018. Data were divided into two samples consisting of 910 patients and 1458 lesions. To assess the association between the variables, the chi-square test was used. This study was approved by the ethics and research committee of UFSM under number CAAE 30155920.5.0000.5346. In the analysis of patients, there was a predominance of males (55.3%), age group 60-79 years (54.7%), farmers (41.8%) and only one diagnosis of BCC in the last 5 years (67.7 %). There was an association between the farming profession and the male gender, multiple diagnoses of BCCs and more than one BCC excised in the last 5 years. As for the analysis of lesions, there was a predominance of the solid histological subtype (52.2%) and involvement of H zone (48.5%), recurrent lesions corresponded to 3.4%, the presence of perineural and angiolymphatic invasion was present in 0.7% and 0.2%, respectively. As for depth, involvement from the hypodermis occurred in 4.5% and surgical margins were compromised in 6.2%. According to the NCCN criteria, 86.8% of the lesions had a high risk of recurrence. There was an association of compromised margins with L zone, high-risk histological subtype, depth from the hypodermis and diameter greater than 20 mm. There was also an association between depth from the hypodermis and L zone, high-risk histological subtype, ulceration, diameter greater than 20 mm, perineural invasion and angiolymphatic invasion. High-risk histological subtypes were associated with age at diagnosis of 60 years or older, L zone, recurrent lesion, diameter greater than 20 mm, and ulceration. Recurrent lesions were associated with compromised margins. The data presented were similar to the data described in the literature. The large number of cases diagnosed during a 5-year period shows the importance of routine dermatological follow-up in populations with risk factors for the development of cutaneous neoplasms. There were limitations because it was a retrospective study and did not have contact with patients, some data were not correctly filled in the medical records and reports, such as the profession and some histopathological data, the latter leading to the exclusion of some lesions.